To be or not to be "green": How can monetary policy react to climate change? - Lena Boneva; Gianluigi Ferrucci; Francesco Paolo Mongelli (European Central Bank (ECB), 2021)
Climate change has profound effects not only for societies and economies, but also for central banks' ability to deliver price stability in the future. This paper starts by documenting why climate change matters for monetary policy: it impacts the economic variables relevant to setting the monetary policy stance, it interacts with fiscal and structural responses and it can generate dislocations in financial markets, which are impossible for monetary policy to ignore. Next, we survey several possible ways central banks can respond to climate change. These range from protective actions to more proactive measures aimed at mitigating climate change and supporting green finance and the transition to sustainable growth. We also discuss the constraints and trade-offs faced by central banks as they respond to climate risks. Finally, focusing on the specific challenges faced by inflation-targeting central banks, we consider how certain design features of this regime might interact with, and evolve in response to, the climate challenge.
Keywords: E52; E58; Q54; 330; climate change; monetary policy; environmental economics; greenfinance; sustainable growth economics